Growth and Yield Response of Groundnut (Arachis hypogaea L.) through Application of Goat Feces Bokashi Fertilizer and Kirinyu with Dose Variations - Radamuri, Vicky Benyamin; Ratu, Pace; Nganji, Marten Umbu; Ndapamuri, Melycorianda Hubi (Prodi Agroteknologi dan Agribisnis - Universitas Kristen Wira Wacana Sumba, 2025)
This study aims to evaluate the growth response and yield of peanut plants (Arachis hypogaea) to the application of bokashi kachung fertilizer at varying doses. The study used a completely randomized design (CRD) consisting of five dose treatments, each repeated four times, resulting in 20 experimental units. The treatments included the application of bokashi fertilizer at doses of 10, 15, 20, and 25 tons/ha. The results showed that bokashi application at 14, 28, and 42 days after planting (DAP) tended to increase plant height and leaf number, although there were no statistically significant differences between doses. However, there was a tendency that higher bokashi fertilizer doses resulted in better plant growth responses. In terms of yield, treatment P4 (25 tons/ha) yielded the highest values for all production parameters, including the number of pods per plant, fresh and dry weight of pods per plant, and weight of 100 seeds. These findings confirm that bokashi fertilizer has potential as an effective organic fertilizer alternative to support peanut growth and production. Therefore, the use of bokashi fertilizer can be a sustainable strategy to enhance agricultural productivity